Research on the Effect of Beijing Metro Line 16 Operation Plan and Improvement Measures - LIU Xuepeng; GONG Zhenchong; YANG Yuhang (Chengshi guidao jiaotong yanjiu)
［Objective］ At present, there are phenomena such as long running intervals, low train load rate, and poor operating economy during weekday morning rush hours of Beijing Metro Line 16. Therefore, it is necessary to analyze the effect of its current operation plan and study improvement measures from the perspective of cost reduction and efficiency improvement. ［Method］ The current station passenger on and off numbers and cross-section passenger volume distribution of Line 16 during weekday morning rush hours are analyzed, passenger flow characteristics in this scenario are studied. Then, based on the requirements of relevant standards and specifications, the train load rate, passenger service, train configuration rate, and precise matching of capacity and volume during weekday morning rush hours of Line 16 are analyzed, and the effect of the current operation plan is obtained. ［Result & Conclusion］ Problems of low passenger service level, non-compliance with standards requirements, and transportation capacity underutilization in the current morning rush hour operation plan of Line 16 need to be solved through measures such as promoting the construction of abandoned projects, adjusting operation schedules, reporting to government regulatory departments, publishing train timetables, and studying flexible formations, to ensure operating cost reduction while maintaining passenger service levels.